Impact of online and face-to-face learning mediums on satisfaction among accounting students in KPTM Bangi / Auni Ardini Aminuddin … [et al.] - Aminuddin, Auni Ardini; Misnan, Siti Nur Aina; Ahmad Hamzah, Muhammad Syahir Al-Nassir; Fadzli, Muhammad Khairul Fardeen; Yahaya, Nor Affidah (2023)
This study aims to investigate the impact of online and face-to-face learning mediums on satisfaction among accounting students in KPTM Bangi. The population of this research is students from Bachelor of Arts (Honors) in Accounting and Finance (BAAF) in Kolej PolyTech Mara Bangi. However, only students enrolled in year 2 and year 3 from BAAF will participate in the sample size of 189 students. The research collects data from survey questionnaires and analyses it using the Statistical Package for the Social Sciences (SPSS) for statistical data analysis. This study discovered a significant relationship between face-to-face and online classes, as well as their impact on student satisfaction among year 2 and year 3 BAAF students at KPTM Bangi. The results showed that both independent factors had a significant impact towards student’s satisfaction. Future researchers shall include the data to other KPTM institutions in different campuses as it is highly likely that the results do not accurately reflect accounting students attending other higher education institutions because the sample was obtained from a single higher education institution. This is because the sample was obtained from a single higher education institution. Other than that, it is possible that the results of this study do not accurately reflect the circumstance in its entirety. This is because the study itself has some limitations. There are students at KPTM Bangi who are enrolled in diploma programs. However, these students are unable to be included in the sample for this research because the nature of their program does not comply with the standard for this research. This study compares the student’s satisfaction on different mediums of study for accounting students, so the student can choose the most effective way to learn. This study visualizes the student’s satisfaction based on different learning mediums.